Mocidade Portuguesa: : discourses, foundation, structure and actions of this training institution of the Salazar’s regime youth - Freitas, Marcos Maurício Costa (Temporalidades, 2021)
This article aims to articulate brief notes concerning the foundation, structure and actions of the Mocidade Portuguesa, in addition to raise some of the discourses that legitimized its creation. In general terms, the Mocidade Portuguesa was a governmental organization dedicated to the youth’s education in patriotic, moral and religious values, as well as promoting that generation’s militarization, which was built based on the tentative of creating a new political elite that would support the Portuguese Estado Novo, implemented in 1993. Born from the ashes of the republic, overthrown on May 28, 1926, this regime was willing to reorganize the country based on financial adjustments and on a new cultural and educative policy of social reengineering, which became possible throughout an extensive transformation on the Portuguese education. One of the first actions taken by the Estado Novo in this field came with the publication of the Decree-law nº 1,941, which established new standards and rules, creating a national and directed education.